2022
DOI: 10.1021/jacs.2c04565
|View full text |Cite
|
Sign up to set email alerts
|

Environment-Driven Coherent Population Transfer Governs the Ultrafast Photophysics of Tryptophan

Abstract: By combining UV transient absorption spectroscopy with sub-30-fs temporal resolution and CASPT2/MM calculations, we present a complete description of the primary photoinduced processes in solvated tryptophan. Our results shed new light on the role of the solvent in the relaxation dynamics of tryptophan. We unveil two consecutive coherent population transfer events involving the lowest two singlet excited states: a sub-50-fs nonadiabatic L a → L b transfer through a conical intersection and a subsequent 220 fs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 55 publications
(81 reference statements)
2
13
0
Order By: Relevance
“…From Table , it is evident that the L b ⇌ L a reaction is much faster than any transition toward the dark state (in line with the available computational and experimental data for aqueous tryptophan , ), with the latter being a virtually irreversible transition which leads to the overall relaxation mechanism of aqueous indole first (perturbed) electronic excited state represented in Figure . Note that the dark to ground state (πσ* → GS) relaxation has not been investigated in this paper as the dark state radiative relaxation is negligible; that is, we can reconstruct the fluorescence data by considering only the L b ⇌ L a interconversion, their radiative relaxations to the ground state, and the L b → πσ* and L a → πσ* (irreversible) transitions (the normalL normalb h ν π σ * and normalL normala h ν π σ * radiative relaxations are fully negligible).…”
Section: Results and Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…From Table , it is evident that the L b ⇌ L a reaction is much faster than any transition toward the dark state (in line with the available computational and experimental data for aqueous tryptophan , ), with the latter being a virtually irreversible transition which leads to the overall relaxation mechanism of aqueous indole first (perturbed) electronic excited state represented in Figure . Note that the dark to ground state (πσ* → GS) relaxation has not been investigated in this paper as the dark state radiative relaxation is negligible; that is, we can reconstruct the fluorescence data by considering only the L b ⇌ L a interconversion, their radiative relaxations to the ground state, and the L b → πσ* and L a → πσ* (irreversible) transitions (the normalL normalb h ν π σ * and normalL normala h ν π σ * radiative relaxations are fully negligible).…”
Section: Results and Discussionsupporting
confidence: 74%
“…This paper will exploit the general model for treating electronic state transitions, focused specifically on charge transfer and intersystem crossing reactions, developed by our group in the past, , to address the above-mentioned relaxation of the excited electronic states of aqueous indole, focusing on the thermodynamics and kinetics of the deactivation processes at the basis of the fluorescence properties of this model molecule. Such an approach has provided accurate results at significantly less computational expense when compared to the more commonly used strategies relying on the calculation of an ensemble of QM/MM trajectories. In fact, the high cost of this latter approach usually limits its applicability to the picosecond time scale, making it unsuitable for the current study. Even though Machine Learning-based approaches enable longer simulations, our method offers a much reduced overall computational cost permitting an extended phase space sampling, an easier implementation, and a robust and coherent quantum treatment, making it an appealing alternative, especially when the other approaches are not feasible.…”
Section: Introductionmentioning
confidence: 99%
“…The excited singlet state of Trp is marked by complex dynamics on the femtosecond time scale, and its deactivation occurs through multiple concurrent pathways, including fluorescence emission (Φ Fl = 0.13), S 1 → T 1 ISC (Φ T = 0.18), ESIPT from the amino group to the excited indole ring, and ionization producing the tryptophan radical cation (Trp •+ , p K a (Indole • -N H + ) = 4.3) ,, and a solvated electron (Φ e = 0.04–0.08) (Figure ). Excited triplet tryptophan ( 3 Trp, τ T = 14.3 μs) induces the production of both O 2 •– and 1 O 2 (Φ Δ Trp = 0.06; D 2 O, λ EX = 266 nm). ,, (Figure a); hence, depending on the surrounding species, other oxidant species such as H 2 O 2 , ozone (O 3 ), and hydroxyl radical (HO • ) can be formed …”
Section: Key Endogenous Photosensitizers and Their Targetsmentioning
confidence: 99%
“…Flash laser photolysis studies in cyclohexane indicated an appreciable N–H bond dissociation yield at 265 nm, , mimicking the gas phase dynamics at ≤263 nm; however, the complexity of the excited state processes increases when indole is dissolved in polar and more strongly interacting solvents such as water. Steady-state fluorescence studies have reported the energetic ordering of the 1 L a and 1 L b states are inverted in water and polar solvents such as ethanol compared to the gas phase. ,,, This originates from the greater permanent dipole moment of the 1 L a state, which is dynamically and more substantially stabilized by solvation than the 1 L b state, as detailed by ultrafast fluorescence up-conversion and TA studies by the groups of Chergui and Cerullo for tryptophan. , Notably, these two studies concentrated on the fast interconversion between the low-lying 1 ππ* states and did not investigate the photoionization channel.…”
Section: Introductionmentioning
confidence: 99%